Qualidade educacional na escola pública básica em situação de exclusão: olhares diversos - Zuchi, Isabelle Augusto (2016)
This research has as objective the analysis of the concepts of different school segments on the concept of quality of education in a municipal scholar education facility located on the outskirts of the City of Cajamar (SP). To support this work, among other authors aligned with currents of emancipatory education, was used the theoretical framework of Paulo Freire, taking as analytical tools the following categories: unfinished, incompleteness, inconclusiveness; dialogue, world reading awareness and fatalism. As methodological procedures for data collection, questionnaires were used, semi-structured interviews, field observation and epistemological circle. This study revealed that the school, represented by the voices of different segments (management, staff, faculty and students) have a fuzzy view of school quality when faced speech produced by their representations with the pedagogical practices in the school routine. This situation produces a fatalistic perspective on the role of education, considering that, in view of these agents, the school environment can do to overcome the time lags in the educational quality of the most excluded segments. On the other hand, parallel to this view, it can be seen, by these same agents, the desire to glimpse another reality in which a school is possible with more respect, enjoyment and education effectively